Innovations in Islamic Religious Education Teaching Methods in the Digital Era - Gunawan, Syahrul; Maryani; Roihan Ramadhan, Muhammad; Arya Yanuar, Fitra; Saidah; Hidayat, Khoirul (Zona Education Indonesia, 2024)
this study investigates the impact of digital innovation on the teaching of Islamic Education (PAI), highlighting how technology enhances learning outcomes and engagement. The research focuses on the integration of interactive learning applications, e-learning platforms, social media, and educational software into PAI instruction. The primary objective is to evaluate how these technological tools affect student understanding, motivation, and accessibility to learning materials. Using a mixed-methods approach, including surveys and interviews with teachers and students, the study reveals that digital tools make PAI more engaging and relevant. Students appreciate the flexibility of e-learning platforms, which allow for personalized learning experiences. However, challenges such as technology access disparities between urban and rural areas, as well as the need for ongoing teacher training, are identified. The findings suggest that while digital innovations have positive effects on PAI, addressing access issues and enhancing teacher competency are crucial for maximizing their benefits. This study underscores the need for continuous investment in technology infrastructure and professional development to ensure equitable and effective digital education in Islamic studies